The impact of corporate governance on corporate social responsibility at the board-level: A critical assessment. (1st April 2021) - Bolourian, Soudabeh; Angus, Andrew; Alinaghian, Leila
Abstract: The purpose of this research is to synthesise and critically evaluate the extant literature investigating the role of board of directors as a core element of corporate governance in corporate social responsibility (CSR) performance. Adopting a systematic review approach, a sample of 67 studies from 18 highly regarded scholarly journals published between 1992 and 2020 is examined. Distinguishing between two board attributes of director characteristics and board structures, our study uncovers similarities and inconsistencies regarding the effects of various board characteristics and board structures on CSR performance. First, our study reveals that these attributes do not work in isolation but interact with each other and the context in which they are embedded in shaping CSR performance. Additionally, our review identifies substantial variation in conceptualisations, theoretical frameworks, the use of measurements and the contexts across studies providing a basis to offer a comprehensive synthesis of dominant scholarly discourses and an organising lens for future scholarship. Highlights: Board attributes do not work in isolation in shaping CSR Performance. Results indicate inconsistent effects of various board attributes on CSR Performance. Country and Industry moderates the effects of board attributes on CSR performance. Different board attributes affect different CSR dimensions differently. Director characteristics and board structures must be separated in examining boards.